A Vocational Reading of Gen 2:15 to Link Theology of Work and Ecotheology Following Escrivá’s Christian Materialism - Emilio Chuvieco; Michal Karnawalski (Religions)
Genesis 2:15 has been widely used to support both a vocational dimension of work and an earth-caring attitude that goes beyond the dominion narrative of Genesis 1:28. However, this verse has not been interpreted to ground the connection between theology of work and ecotheology. Based on the concept of Christian materialism proposed by Saint Josemaría Escrivá, we give a new interpretation to this biblical passage in order to ground the human vocation to work by linking it to the need to care for or preserve the earth. Therefore, the transformation of creation that most professional activities carry out is qualified by the duty to do it with “care”, that is, to transform the natural world with due respect for God’s original creative plan. In this way, work can become co-creative, and the transformation of nature that work entails is linked to a divine call to develop it with respect for the inner meaning of all creatures.